Human and environmental impact of chemical agents used for cleaning, antisepsis, disinfection and sterilization in healthcare facilities. A semi-qualitative study among medical institutions of Puglia and Basilicata, southern Italy - Lattanzio, Sabrina; Cuscianna, Eustachio; Riformato, Giacomo; Noviello, Chiara; Tafuri, Silvio; Bianchi, Francesco Paolo (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The widespread use of sanitizers and disinfectants has raised concerns about their potential environmental toxicity. As these substances are dispersed in diverse environments, they interact with ecosystems and natural elements, potentially leading to ecological consequences. The careful management of disinfectants in healthcare settings plays a crucial role, embodying the principles of sustainability and responsible healthcare. Methods: This study focused on the characteristics of sanitizers and disinfectants used in healthcare facilities in Puglia and Basilicata, southern Italy. From June to July 2023, we requested the list of these products from the health directorates of major healthcare facilities in the two regions. Our study aims to identify the types of sanitizers and disinfectants in use, their chemical compositions, and their potential human and environmental impacts. Results: Among the 72 disinfectants and sanitizers analyzed, a concerning observation emerged. Data on the toxicity related to human exposure were not reported for 35.9% of the analyzed disinfectants and sanitizers. Information on environmental impact and toxicity data was missing for 27.8% of the products. The lack of information on the potential impact of these sanitizers raises alarms, especially considering the urgency of addressing global environmental concerns. Conclusions: The integration of health, safety, and environmental is crucial for the sustainable and high-quality development of human society. The sustainable and responsible use of disinfectants and sanitizers requires a holistic approach that considers both human safety and environmental well-being. Adopting solutions that prioritize public health and environmental sustainability is imperative for a healthier and resilient future.